The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.5466/ijoms.15.107
|View full text |Cite
|
Sign up to set email alerts
|

<b>Pro-inflammatory Cytokine Production in Co-culture of Human Monocytes and Synovial Fibroblasts from the Human Temporomandibular Joint </b>

Abstract: The synovial membrane is composed of fibroblast-like cells (synovial fibroblasts) and macrophage-like cells. Synovial fibroblasts and monocytes/macrophages are believed to interact and to play a critical role in the development of synovial inflammation. In this study, we investigated the protein production of pro-inflammatory cytokines in co-culture of synovial fibroblasts isolated from the temporomandibular joint (TMJ) and monocytes isolated from peripheral blood. Monocytes that had attached to the plastic su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Moreover, higher degrees of IL-1α and IL-1β in the synovial fluid of patients with TMD were indicated in various works of research [27]. Meanwhile, few studies examined fibroblasts, which were cultured from TMJ synovial fluid [32,35] and TMJ synovial biopsies (immunohistochemistry) [46,52], leading to consistent results. Furthermore, a study by Ok et al 2018 [34] demonstrated that the level of urinary pyridinoline (PYD) and deoxypyridinoline (DPD) were increased in patients with TMDs.…”
Section: Tmds Inflammatory Biomarkersmentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, higher degrees of IL-1α and IL-1β in the synovial fluid of patients with TMD were indicated in various works of research [27]. Meanwhile, few studies examined fibroblasts, which were cultured from TMJ synovial fluid [32,35] and TMJ synovial biopsies (immunohistochemistry) [46,52], leading to consistent results. Furthermore, a study by Ok et al 2018 [34] demonstrated that the level of urinary pyridinoline (PYD) and deoxypyridinoline (DPD) were increased in patients with TMDs.…”
Section: Tmds Inflammatory Biomarkersmentioning
confidence: 95%
“…Moreover, several synovial, serum and urinary proteins were found to exhibit important diagnostic tool for TMDs (Table 1). [33] Wilkes classification Synovial fluid IL-8, sTNFR1, sTNFR2 and sIL-6R Ok et al, 2018 [34] RDC-TMD Urine PYD and DPD Watanabe et al, 2017 [35] Arthroscopy of the TMJ TMJ synovial fibroblasts IL-1β, IL-6, and IL-8…”
Section: Tmds Inflammatory Biomarkersmentioning
confidence: 99%